Delineating the novel effects of Aspalathus linearis (Rooibos) on mitochondrial regulation in an in vitro model of angiotensin-II induced hypertrophy and apoptosis - Kgatla, Thato Mmathapelo (Stellenbosch : Stellenbosch University, 2025)
Kgatla, T. M. 2025. Delineating the novel effects of Aspalathus linearis (Rooibos) on mitochondrial regulation in an in vitro model of angiotensin-II induced hypertrophy and apoptosis. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/d70588d8-bdf1-4cf7-b45d-390cc22d85eb